ANALISIS STRATEGI AMERIKA SERIKAT DALAM UPAYA COUNTERTERRORISM TERHADAP KELOMPOK ISIS DI WILAYAH TIMUR TENGAH PERIODE DONALD TRUMP PADA TAHUN 2017 - 2019 - Rafli Akbar Maulani, (2023)
The threat of terrorism continues to be a real threat to the United States, changing presidents has also changed its terrorist groups. Donald Trump, who has just served as President of the United States in 2017, must also be faced with a sizeable problem, namely ISIS. The threat posed by ISIS is enormous considering that the group also still has close ties with Al-Qaeda, the main perpetrator of 9/11. ISIS's actions also made the United States feel that the terrorist group could not be left alone, so the United States under the leadership of Donald Trump used several strategies to eradicate ISIS. In this study the author will discuss the United States' strategy in counterterrorism effort against the ISIS group. The strategy that is carried out is of course with the aim of extinguishing the fire from ISIS. This study uses exploratory qualitative methods. Researchers used several journal articles as well as official United States government report documents to complete the required data. In this study, the authors also use several theories, including theory of Counterterrorism, and Securitization. The results of the study show that the United States strategy led by Donald Trump has positive results. This can be proven by the containment of the ISIS movement and the stabilization of the victims.